Sistem Informasi Geografis Pemetaan Lokasi Jaringan Internet Kampus Universitas Malikussaleh Bukit Indah Berbasis Web Menggunakan Leaflet Javascript - Fatimah Zahra, Safwandi, Sujacka Retno (Jurnal Elektronika dan Teknologi Informasi, 2024)
Geographic Information System (GIS) is a system used to process and store geographic data. This research encountered several issues regarding how to map the campus internet network of Malikussaleh University Bukit Indah using GIS and how to design a web-based GIS system for mapping the location of the internet network on the campus of Malikussaleh University Bukit Indah. The aim of this research is to provide a way to map the internet network on the campus using GIS and design a web-based GIS system for mapping the location of the internet network, with the target audience being all residents of Malikussaleh University. The research method applied is descriptive qualitative research, which means that this research focuses on analysis based on data obtained from sources. The goal is to provide an overview of the problem being studied, while for the system development method, the waterfall model approach was chosen. The result of this research creates an information system in the form of a map that contains the distribution of the internet network location on the campus of Malikussaleh University Bukit Indah based on a website using the Leaflet JavaScript library. This research also produces a system that can quickly detect trouble on the network because the system is directly connected to email, which can generate notifications to the admin email if users add complaint data.